2009
DOI: 10.5650/jos.58.467
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of N,N'-Carbonyl Difatty Amides from Palm Oil

Abstract: N,N'-Carbonyl difatty amides (CDFAs) have been synthesized from palm oil using sodium ethoxide as catalyst. Ethyl fatty esters (EFEs) were produced as a by-product as well as glycerol. The synthesis was carried out by reflux palm oil and urea in presence of ethanol. In this process, palm oil gave 79% pure CDFAs after 8 hours and molar ratio of urea to palm oil was 6.2: 1 at 78 . Both CDFAs and EFEs have been characterized using elemental analysis, Fourier transform infrared (FTIR) spectroscopy and 1 H nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Other uses include, synthesized a series of alkyloxybenzoyl hydroxamic acids and fatty acyl hydroxamic acids and found that some of these chemicals possessed antifungal activity [7][8][9] . Several studies were carried out for synthesis of hydroxamic acids from acids and esters with hydroxyl amine [10][11][12][13] . Servat et al (1990) reported that the synthesis of alkanohydroxamic acids (N-acyl hydroxylamines) by Rhizomucor miehei lipase -catalyzed hydroxylaminolysis of fatty acids and soybean methyl ester 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Other uses include, synthesized a series of alkyloxybenzoyl hydroxamic acids and fatty acyl hydroxamic acids and found that some of these chemicals possessed antifungal activity [7][8][9] . Several studies were carried out for synthesis of hydroxamic acids from acids and esters with hydroxyl amine [10][11][12][13] . Servat et al (1990) reported that the synthesis of alkanohydroxamic acids (N-acyl hydroxylamines) by Rhizomucor miehei lipase -catalyzed hydroxylaminolysis of fatty acids and soybean methyl ester 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Fatty amides were synthesized from fatty acids with urea instead of ammonia or other amidation reactant using Candida antartica lipase (Novozyme 435) as a catalyst at 60 for 48 h and atmospheric pressure 13) . It was reported in our previous paper 14) that N, N' carbonyl difatty amides were synthesized by refluxing palm oil and urea using sodium ethoxide as a catalyst in the presence of ethanol at 78 for 8 h. Our literature search shows that there is no information regarding enzymatic synthesis of fatty amides directly from palm olein and urea.…”
Section: Introductionmentioning
confidence: 91%
“…The first commercial clay nano-composite was prepared via an ion exchanging process (Ray and Okamoto, 2003;Giannelis, 1996). Recently, many studies were reported for MMT modification using alkylammonium ions produced from vegetable oils (Al-Mulla et al, 2009;Al-Mulla et al, 2010a;Hoidy et al, 2010a;Hoidy et al, 2010b).…”
Section: Modification Of Claymentioning
confidence: 99%